Tax Literacy Trumps Digitalization: The Key Driver of Employee e-SPT Filing Compliance - Akbar Albastiah, Fauzan; Isnaen , Fauzi (Journal of Economics and Social Sciences (JESS), 2025)
This study analyzes the effect of digitalization of the tax administration system and tax literacy on employees' annual e-SPT reporting at PT. Daiki Aluminium Industry Indonesia. Using a quantitative associative approach, the research collected data from 80 employees who are individual taxpayers through questionnaires. The data were analyzed using multiple linear regression. The results indicate that both digitalization of the tax administration system and tax literacy have a positive and significant effect on annual e-SPT reporting, both partially and simultaneously. These findings highlight the importance of training and disseminating information about digital tax systems to improve tax compliance. The study also identifies challenges such as technical issues and gaps in understanding, emphasizing the need for enhanced support and education for taxpayers.